The valley of lost secrets - Parr, Lesley (Bloomsbury Children's Books, 2021)
"September 1939. When Jimmy is evacuated to a small village in Wales, it couldn't be more different from London. Green, quiet and full of strangers, he instantly feels out of place. But then he finds a skull hidden in a tree, and suddenly the valley is more frightening than the war. Who can Jimmy trust? His brother is too little; his best friend has changed. Finding an ally in someone he never expects, they set out together to uncover the secrets that lie with the skull. What they discover will change Jimmy - and the village - forever."--Back cover